Cost per Responder Analysis of Secukinumab versus Adalimumab in the Treatment of Psoriatic Disease - Paolo Gisondi; Davide Geat; Martina Maurelli; Luca Degli Esposti; Francesco Bellinato; Giampiero Girolomoni (Vaccines, 2022)
Background: The EXCEED study evaluated the efficacy and safety of secukinumab versus adalimumab in psoriatic arthritis, but it did not include a pharmacoeconomic analysis. The objective of this study was to compare the cost per responder of secukinumab versus adalimumab in patients with psoriatic disease. Methods: The cost per responder was calculated by multiplying the cost of treatment by the number needed to treat for each therapy. The 52-week primary endpoint was the American College of Rheumatology response rate (ACR) 20; secondary endpoints were ACR 50, Psoriasis Area and Severity Index (PASI) 90, and minimal disease activity (MDA). Results: The cost per responder for ACR 20 was €19,846 versus €19,766 for secukinumab and adalimumab, respectively, whereas the costs per responder for ACR 50 and PASI 90 were €27,820 versus €27,384 and €22,102 versus €32,375 for secukinumab and adalimumab, respectively. The cost per MDA responder was €34,072 and €38,906 for secukinumab versus adalimumab. Conclusions: The costs per responder associated with the psoriatic arthritis end points were similar for adalimumab and secukinumab; conversely, the costs for psoriasis and composite end points were lower for secukinumab.